2016
DOI: 10.1080/15592294.2016.1255385
|View full text |Cite
|
Sign up to set email alerts
|

PEG3 binds to H19-ICR as a transcriptional repressor

Abstract: Paternally expressed gene 3 (Peg3) encodes a DNA-binding protein with 12 C2H2 zinc finger motifs. In the current study, we performed ChIP-seq using mouse embryonic fibroblast (MEF) cells. This experiment identified a set of 16 PEG3 genomic targets, the majority of which overlapped with the promoter regions of genes with oocyte expression. These potential downstream genes were upregulated in MEF cells lacking PEG3 protein, suggesting a potential repressor role for PEG3. Our study also identified the imprinting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…We also performed a similar series of expression analyses for the following genes: Oxtr , Avp , Oxt , Peg10 and Msl1 ( Fig 5 ). The three genes ( Oxtr , Oxt and Avp ) and Peg3 have been shown to be involved in maternal-caring behaviors and controlling the volume of bodily fluids [ 23 , 24 ], while Msl1 and Peg10 are known to be downstream targets of Peg3 [ 25 27 ]. For this series of expression analyses, we used male (n = 3) and female (n = 3) cDNA sets that had been generated using the total RNA from neonatal heads and adult hypothalamus.…”
Section: Resultsmentioning
confidence: 99%
“…We also performed a similar series of expression analyses for the following genes: Oxtr , Avp , Oxt , Peg10 and Msl1 ( Fig 5 ). The three genes ( Oxtr , Oxt and Avp ) and Peg3 have been shown to be involved in maternal-caring behaviors and controlling the volume of bodily fluids [ 23 , 24 ], while Msl1 and Peg10 are known to be downstream targets of Peg3 [ 25 27 ]. For this series of expression analyses, we used male (n = 3) and female (n = 3) cDNA sets that had been generated using the total RNA from neonatal heads and adult hypothalamus.…”
Section: Resultsmentioning
confidence: 99%
“…For this and the current study, MEFs have been selected as an in vitro system of choice since Peg3 is highly expressed in this homogenous cell population [14]. The paternal transmission of the CoKO (Conditional KnockOut-ready) allele is designed to deplete the majority of the PEG3 protein owing to the transcriptional truncation of Peg3 at the 5 th intron [7].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of protein function, the ORF (Open Reading Frame) of PEG3 contains several protein motifs that are frequently associated with DNA-binding proteins, such as SCAN and KRAB-A boxes at the N-terminal portion and C2H2-Kruppel-type zinc finger motifs at the C-terminal portion [911]. Consistent with this, genome-wide ChIP-seq analyses have indeed identified many genomic targets as its downstream genes [1214]. Several series of in vitro analyses further revealed that PEG3 is a transcriptional repressor for the downstream genes [1215], and also that the PEG3-driven repression may be mediated through the interaction with a co-repressor protein KAP1 (Kruppel-associated protein 1) [11].…”
Section: Introductionmentioning
confidence: 96%
“…PEG3 also contains a KRAB-A domain, thus is predicted to be a transcriptional repressor through its interaction with KAP1 [ 8 ]. This predicted repression function has been further confirmed through the observation that the expression levels of its downstream genes are usually up-regulated in the tissues of the mouse mutant models targeting Peg3 [ 6 , 7 ]. According to the results from mouse knockout (KO) models, Peg3 is also involved in controlling fetal growth rates and maternal-caring behaviors [ 9 13 ].…”
Section: Introductionmentioning
confidence: 84%